Emancipatory futures: women and agitational politics in revolutionary Egypt - Abdel-lateef, Shaza Zaher (AUC Knowledge Fountain, 2013)
This thesis investigates the gender dynamics in the Egyptian 25th of January 2011 revolution. It explores the centrality of gender relations in different configurations of the Egyptian revolution. It argues, that in order to provide satisfying analysis of the different events between January 2011 and April 2013, the period that the research focuses on, it is crucial to analyze gender relations that played a critical role in the toppling of the system "Iskat-El-Nizam". The importance of this thesis stems from the fact that it maps most of the struggles, mobilization and terrains that woman activists chose or had to go through since the ousting of Mubarak until the moments of writings. It argues that the revolution was not concluded by the inauguration of a new president in June 2012, and that different paths are still being tested. After exploring the gender component during the 18 days of Tahrir, it turns its focus to the main camps and trajectories that women activists have taken, which includes their concerns about writing the new constitution of Egypt, in addition, to the struggle against the systemic violence and sexual assaults against female protesters. It also provides a panoramic overview of many of the new women groups and movements that have emerged in the post-Mubarak period, by analyzing their approaches to engagement, mobilization, new tendencies, and strategies adopted to cope with struggles they face with respect to the gender discourse, with particular focus on the debates aimed to blame, victimize and marginalize women. It also paves the way for future research on key debates and landmarks that have been spotted in this thesis in order to investigate how women activism in Egypt will develop in the future.